Determinants of perceived sleep quality in normal sleepers. Issue 4 (4th July 2019) - Goelema, M. S.; Regis, M.; Haakma, R.; van den Heuvel, E. R.; Markopoulos, P.; Overeem, S.
ABSTRACT: Objective : This study aimed to establish the determinants of perceived sleep quality over a longer period of time, taking into account the separate contributions of actigraphy-based sleep measures and self-reported sleep indices. Methods : Fifty participants (52 ± 6.6 years; 27 females) completed two consecutive weeks of home monitoring, during which they kept a sleep–wake diary while their sleep was monitored using a wrist-worn actigraph. The diary included questions on perceived sleep quality, sleep–wake information, and additional factors such as well-being and stress. The data were analyzed using multilevel models to compare a model that included only actigraphy-based sleep measures (model Acti) to a model that included only self-reported sleep measures to explain perceived sleep quality (model Self). In addition, a model based on the self-reported sleep measures and extended with nonsleep-related factors was analyzed to find the most significant determinants of perceived sleep quality (model Extended). Results : Self-reported sleep measures (model Self) explained 61% of the total variance, while actigraphy-based sleep measures (model Acti) only accounted for 41% of the perceived sleep quality. The main predictors in the self-reported model were number of awakenings during the night, sleep onset latency, and wake time after sleep onset. In the extended model, the number of awakenings during the night and total sleep time of the previous night were the strongest determinants of perceived sleep quality, with 64% of the variance explained. Conclusion : In our cohort, perceived sleep quality was mainly determined by self-reported sleep measures and less by actigraphy-based sleep indices. These data further stress the importance of taking multiple nights into account when trying to understand perceived sleep quality.